The skin microbiome as a new potential biomarker in the domestication and health status of Octopus vulgaris - Costas-Imbernón, Daniel; Costas-Prado, Carolina; Sequeiro, Teresa; Touriñán, Pablo; García-Fernández, Pablo; Tur, Ricardo; Chavarrías, David; Saura, María; Rotllant, Josep (Frontiers in Marine Science, 2024)
Over the past decade, there has been a growing interest in common octopus aquaculture, prompted by several factors such as the increase in market demand, the decline in overall fisheries and the search for more sustainable food resources. Nevertheless, this interest has raised concerns about the potential impact of large-scale production and intensified farming practices in the future. This study aims to establish a baseline understanding of the natural microbial communities that inhabit skin mucus of the common octopus, describe its core microbiota, and assess the impact of captive rearing on these communities and animal welfare. The skin microbiome of wild-captured octopuses was compared with that of reared in aquaculture using 16S ribosomal RNA metabarcoding. The findings show that the core microbiota of octopus mucosal skin is dominated by the phyla Bacteroidota and Pseudomonadota, with Aurantivirga, Pseudofulvibacter, and Rubritalea being the most abundant genera. Despite differences in abundance, the microbiota composition and diversity between wild and aquaculture octopuses were similar. Wild samples had an enrichment of Gammaproteobacteria, including potentially pathogenic species such as Vibrio spp., Photobacterium swingsii, and Lactococcus garvieae, which were less prevalent or absent in aquaculture samples. KEGG functional pathways predictions indicated a higher enrichment in functional pathways related to xenobiotic remediation in wild samples, reflecting their need to adapt to a more variable and potentially contaminated environment. This is the first study to characterize the mucosal skin microbiome of the common octopus and to compare wild and aquaculture specimens. The results suggest that current aquaculture practices support animal welfare through the use of controlled hatchery environments and high-quality water conditions. These insights are valuable for the development of sustainable and responsible aquaculture practices, with the octopus microbiome serving as a potential biomarker for health status and animal welfare.